Temporal Deictic Expressions in the Song Lyrics of Pale Waves’ My Mind Makes Noises Album - Ida Ayu Rai Nayma Mahadewi; Ni Luh Sutjiati Beratha; Sang Ayu Isnu Maharani (Stilistika : Journal of Indonesian Language and Literature, 2023)
"Temporal Deictic Expressions in the Song Lyrics of Pale Waves’ "My Mind Makes Noises" Album" is the title of this article. This article focused on temporal deictic expressions in "My Mind Makes Noises" song lyrics that have official music videos. This article had two aims: first, to identify the temporal deictic expressions in the album's song lyrics; and second, to explain and analyze the deictic usages of the album's temporal deictic expressions. This article used a qualitative method and content analysis technique to analyze the data, with Huang's pragmatics theory as the grand theory and Halliday's context of situation theory as the supporting theory. The data for this article was gathered through the use of documentation and note-taking method and technique. This article used an informal method and descriptive technique to present the analysis, which means the results were presented in the form of descriptive words and sentences. There were six temporal deictic expressions analyzed in this article, which were then categorized into three categories based on the time of the event using pragmatics method, the context of the situation, and then the deictic usage of each temporal deictic expression. This article demonstrated that gestural deictic usage offers a clearer identification of the time of the event in temporal deictic expression, as well as an easier understanding of the context of situation.